A Culturally Appropriate Self-Management Program for Hispanic Adults With Type 2 Diabetes and Low Health Literacy Skills. (March 2017) - Brunk, Debra R; Taylor, Ann Gill; Clark, Myra L.; Williams, Ishan C.; Cox, Daniel J.
Purpose: This study assessed the feasibility of adapting a patient-centered educational intervention for type 2 diabetes (T2D) self-management for a Hispanic population with low health literacy skills.Design: A descriptive qualitative study design and phenomenological analyses were used. Nine Hispanic adults with T2D recruited from a rural community health center participated in an educational program that instructed on low glycemic food choices, meaningful glucose self-monitoring, and physical activity to decrease blood glucose spikes. Participants' feedback was recorded during four 2-hour focus group sessions.Findings/Results: Participants' feedback clustered around four themes: information and knowledge, motivation and barriers to change, experiences with new behaviors, and personal responsibility.Discussion/Conclusions: Data support the feasibility of adapting an established health-enhancing approach for promoting self-management of T2D to a low health literacy Spanish-speaking population.Implications for Practice: The findings may help in further development of tools and strategies for improved T2D self-management in the study population.